Expression of TAD1 (Tillering & Dwarf1) Gene in Hawara Bunar and IR64 Rice Cultivars: Expression of TAD1 (Tillering & Dwarf1) Gene in Hawara Bunar and IR64 - Sindiya, Vita; Fendiyanto, Miftahul Huda; Hamim, Hamim; Miftahudin , Miftahudin (Journal of Tropical Life Science, 2024)
Rice cv. Hawara Bunar is a local rice cultivar tolerant to aluminum (Al) and drought stress. However, the cultivar has inferior characteristics, such as a tall habitus and a small number of tillers, making the cultivar agronomically unattractive. Many genes control plant height and tiller number; one is the TAD1 gene. Analysis of gene expression in two contrasting rice cultivars for both characters is a prerequisite for selecting certain genes for gene editing targets. This study aimed to analyze the gene expression of the TAD1 in rice cv. IR64 and Hawara Bunar, and to construct a phylogenetic tree of genes that regulate rice plant height and tiller number. Gene expression analysis was conducted using the qRT-PCR technique, while the phylogenetic tree was constructed based on the Neighbor-Joining method using PAUP4 software. The results showed TAD1 gene expression in the tillering phase of rice cv. Hawara Bunar is higher than the cv. IR64. The gene expression level in both cultivars corresponds to the plant height and tiller number characters in both rice cultivars. Phylogenetic analysis showed that the TAD1 gene clustered with genes that cause the rice to have a tall habitus with few tillers. The results of a transcriptome meta-analysis reinforced the phylogenetic tree, which shows that the TAD1 gene was found in a group of downregulated genes based on the volcano plots. Therefore, the TAD1 gene can be selected as a target gene for editing in rice cv. Hawara Bunar to obtain superior characters.